(untitled) (Research, Society and Development, 2020)
This work aims to characterize the perceptions of agroecological and conventional farmers, living in the North of Rio Grande do Sul, about the ecosystem functions and services of the forests. 120 farmers had participated in the research, 60 conventional and 60 agroecological. The data collection was carried out through a structured interview, whose data were subjected to statistics. Agroecological and conventional farmers recognize that forests provide numerous environmental functions (regulation, provision, habitat and information). The functions of regulation and provision were the most cited, and there are differences in the percentage of citations between agroecological and conventional farmers. The results that, the older were the interviewee, the number of citations related to the regulatory services decreases, and the number of citations of the provision services increases. It is concluded that the farmers in the studied region have an understanding of the importance of forests for human well-being and for the productive activities they carry out. This understanding is broader and deeper among agroecological farmers, among those who are younger and have a higher level of education.